2000
DOI: 10.1080/001401300184459
|View full text |Cite
|
Sign up to set email alerts
|

Posture, discomfort and performance in a VDT task

Abstract: Improvements in workplace, working posture, and discomfort need to be justified in terms of improvements in performance. Previously, a visual inspection task has been investigated. The objective of the current study was to demonstrate the interactions between workplace, work duration, discomfort, working posture, as well as performance in a 2-h typing task. Three levels of keyboard heights were used to change working posture (e.g. joint angles and postural shifts), and thus presumably discomfort (e.g. rating o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(66 citation statements)
references
References 18 publications
4
62
0
Order By: Relevance
“…Previous cross-sectional studies have indicated that discomfort and high perceived exertion may be associated with increased risks for musculoskeletal neck and upper extremity symptoms/disorders (Hsu and Wang, 2003;Karlqvist et al, 2002;Liao and Drury, 2000;Ortiz-Hernandez et al, 2003). Results from study IV confirmed these cross-sectional findings by showing that perceived exertion and, to a certain extent, perceived comfort during computer work are predictors for the development of neck and upper extremity symptoms.…”
Section: Perceived Exertion Comfort Neck and Upper Extremity Symptosupporting
confidence: 71%
“…Previous cross-sectional studies have indicated that discomfort and high perceived exertion may be associated with increased risks for musculoskeletal neck and upper extremity symptoms/disorders (Hsu and Wang, 2003;Karlqvist et al, 2002;Liao and Drury, 2000;Ortiz-Hernandez et al, 2003). Results from study IV confirmed these cross-sectional findings by showing that perceived exertion and, to a certain extent, perceived comfort during computer work are predictors for the development of neck and upper extremity symptoms.…”
Section: Perceived Exertion Comfort Neck and Upper Extremity Symptosupporting
confidence: 71%
“…It would suggest that management should perhaps focus on the patient's workstation, work postures, and behaviors. Support for this approach extends from the results of recent studies, which found the following: good working technique (defined as having forearm support, smooth movements when using mouse or keyboard, and relaxed shoulders) was associated with reduced muscular load of the forearm extensor muscles; 38 screen height influenced muscle activity of the cervical spine; 57 keyboard height changed working postures; 37 and physical symptoms of headache, stiff shoulders, and low back pain increased with increasing duration of daily computer use. 49 These findings would indicate that an occupational and ergonomic intervention approach might be beneficial in alleviating both the symptoms of lateral epicondylalgia as well as accompanying cervical symptoms.…”
Section: Discussionmentioning
confidence: 90%
“…However, after they change comfortable chairs with appropriate dimensions or change their postures, their work efficiency is improved unexpectedly. The work efficiency improvement due to comfortable chairs proves the statement [1][2] of ergonomics. At the same time, sitting for a long time and poor sitting postures adversely influence the human health, with an intensifying trend.…”
Section: Introductionmentioning
confidence: 76%